Pengaruh Jenis dan Konsentrasi Bahan Penstabil terhadap Karakteristik Fisikokimia dan Sensori Ready to Drink Parijoto - Handayani, Isti; Septiana, Aisyah Tri; Salsabila, Muna Verentsya (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2026)
Parijoto (Medinilla speciosa), a native Indonesian fruit with potential health benefits, has limited utilization due to its short shelf life, firm texture, and sour taste. Processing parijoto into a ready to drink (RTD) beverage is a potential strategy to improve its usability and product value. However, the stability of fruit juice beverages depends on maintaining a homogeneous mixture of juice, water, and other ingredients; therefore, stabilizers are required to ensure product quality. This study aimed to evaluate the effects of stabilizer type and concentration on the physicochemical and sensory characteristics of parijoto RTD beverages. A factorial completely randomized design (CRD) was applied with two factors: stabilizer type (carboxymethyl cellulose/CMC, pectin, and a CMC–pectin mixture) and stabilizer concentration (0.25, 0.50, and 0.75%). Physical characteristics analyzed included viscosity, while chemical parameters consisted of pH, total soluble solids, and reducing sugars. Sensory evaluation was conducted using a preference test. The results showed that stabilizer type and concentration significantly affected viscosity, pH, and total soluble solids of the RTD beverage (p<0.05). A significant interaction between stabilizer type and concentration was also observed for viscosity, pH, reducing sugar content, total soluble solids, and sensory preference. The best formulation was obtained with the addition of 0.25% CMC, producing a beverage with viscosity of 9.80 cP, pH 2.92, total soluble solids of 12.99 °Brix, reducing sugar content of 3.74%, and a sensory preference score of 3.78, indicating a favorable level of consumer acceptance. These findings suggest that CMC at low concentration can effectively improve the stability and acceptability of parijoto RTD beverages.